Capital and Social Difference in Gramsci and Luxemburg. Issue 1 (2nd January 2019) - Wainwright, Joel
Abstract : Antonio Gramsci's prison notebooks are widely celebrated for their theorization of the political and of hegemony in capitalist society. We may also read the notebooks as works analyzing conditions where capitalist social relations are prevalent, but where pre- and noncapitalist social relations have only partially decomposed. This opens the way for situating them alongside Rosa Luxemburg's less well-known writings, including her unpublished prison manuscript "Introduction to Political Economy." Her analysis of the political and imperial dynamics of capitalist societies centers upon the question of the origins and formation of capitalist social relations. Although his prison notebooks suggest a capacious interest in global dynamics, Gramsci's focus is generally Italy, and the complexities of transition are thereby narrowed. By contrast Luxemburg's writings on political economy—like Gramsci's, left incomplete by her imprisonment and subsequent murder by fascists—consistently emphasize the historical evolution of distinct social formations, their geographical diversity, and the importance of the specific emergence of capitalist social relations from precapitalist societies.